2015
DOI: 10.1530/edm-15-0034
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cervical haemorrhage of a parathyroid adenoma

Abstract: SummaryHaemorrhage of a parathyroid adenoma is a rare clinical presentation. This report describes a previously fit and well 54-year-old woman who presented with acute neck swelling and pain with an overlying ecchymosis. Admission laboratory tests revealed a raised parathyroid hormone and hypercalcaemia. A computed tomography (CT) scan showed widespread anterior cervical haemorrhage and a lesion at the inferior pole of the left thyroid gland. A working diagnosis of spontaneous haemorrhage from a parathyroid ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…This patient's presentation was very similar to previous case reports of spontaneous hemorrhage secondary to a parathyroid adenoma [9] —mostly localized as seen with her cervical and mediastinal hemorrhage and symptoms of globus and dysphagia. Like previous studies, she was also of the common demographic of middle-aged women who are otherwise healthy and have relatively asymptomatic hyperparathyroidism.…”
Section: Discussionsupporting
confidence: 85%
“…This patient's presentation was very similar to previous case reports of spontaneous hemorrhage secondary to a parathyroid adenoma [9] —mostly localized as seen with her cervical and mediastinal hemorrhage and symptoms of globus and dysphagia. Like previous studies, she was also of the common demographic of middle-aged women who are otherwise healthy and have relatively asymptomatic hyperparathyroidism.…”
Section: Discussionsupporting
confidence: 85%
“…This case, in terms of clinical and paraclinical characteristics, has many similarities with other cases related to hemorrhage from parathyroid tumors that have been recorded around the world. 1,4 The bone and kidney symptoms of this patient are very typical for primary hyperparathyroidism, and besides, the elevation of PTH and calcium enhance the confirmation of this diagnosis. The disease progression with previous pain and swelling in the neck area and bruises in the chest, neck, and abdomen suggested that the cause could be the rupture of the thyroid or parathyroid.…”
Section: Discussionmentioning
confidence: 66%
“…Hemorrhage outside the parathyroid glands without risk factors is very rare. 1 The clinical presentation of cervical hemorrhage caused by the rupture of parathyroid tumors was first described by Capps in 1934 after one death due to this cause. 2 Although rare, the disease progresses seriously and could cause death easily.…”
Section: Introductionmentioning
confidence: 99%
“…3 7 Ulrich et al argued that patients with VC involvement should be operated within a month, minimising the risk of re-bleeding and recurrent laryngeal nerve injury secondary to tethering. 27 From our review, VC immobility was described in six patients on initial FNE. 3 9 12 16 32 Four patients underwent surgery within 4 weeks, of initial presentation 9 16 26 32 with VC paralysis persisting in two cases.…”
Section: Lessons Learnedmentioning
confidence: 92%